Development of Ready-to-Cook (Rtc) Hilsa (Tenualosa Ilisha) Curry Under Vacuum and Modified Atmosphere Packaging During Refrigerated Storage (Journal of Bio-Science, 2021)
The aim of the study was to evaluate quality of ready-to-cook (RTC) hilsa curry under not sealed pack as control, vacuum as T1, MAP-1 (50% CO2 & 50% N2) as T2, and MAP-2 (40% CO2 , 30 N2 & 30% O2) pack as T3 during storage at 4±1°C. For this purpose, pH, total volatile base nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS) and aerobic plate count (APC) of three samples from each treatment were analyzed at four days interval during 28 days of storage. The pH and TVB-N values of RTC hilsa curry were within the standard limit in all samples during the storage period. However, significantly (p